Obravnava bolnice z motnjami srčnega ritma zaradi zastrupitve z metildigoksinom - Jovanović, Mark (Medicinski razgledi, 2023)
Despite the advances in the pharmacotherapy of heart failure with reduced ejection frac- tion and atrial fibrillation synthetic cardiac glycosides continue to be used for the adju- vant treatment of these patients. Digoxin and metildigoxin are the only two synthetic cardiac glycosides registered in Slovenia, and treatment with digoxin requires regular therapeutic drug monitoring. High serum digoxin level and digoxin intoxication are often used interchangeably to define serum digoxin concentration beyond therapeutic range. However, digoxin intoxication is a term used to emphasize the presentation of symptoms related to high serum digoxin level. Life-threatening arrhythmias present the leading cause of death due to digoxin toxicity. Proper understanding of the pathophysiological mechanism of arrhythmogenesis due to digoxin toxicity, with sinus bradycardia being more commonly associated with digoxin intoxication than bundle blocks, leads to early recognition of intoxicants with subtle clinical presentation and, therefore, faster treat- ment and good clinical outcome of those patients. The following case report presents a fema- le patient with several risk factors for metildigoxin intoxication and the acute management of cardiac arrhythmias due to metildigoxin toxicity and drug-drug interaction.
Keywords: aritmija; arrhythmia; metildigoksin; metildigoxin; sintetični srčni glikozidi; synthetic cardiac glycosides